2017
DOI: 10.1002/ar.23602
|View full text |Cite
|
Sign up to set email alerts
|

From Biography to Osteobiography: An Example of Anthropological Historical Identification of the Remains of St. Paul

Abstract: In the identification process of historical figures, and especially in cases of Saint's bodies or mummified remains, any method that includes physical encroachment or sampling is often not allowed. In these cases, one of the few remaining possibilities is the application of nondestructive radiographical and anthropological methods. However, although there have been a few attempts of such analyses, no systematic standard methodology has been developed until now. In this study, we developed a methodological appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
8
0
1
Order By: Relevance
“…Thus, in a similar approach as other studies verifying the authenticity of religious relics (Alterauge et al, 2016; Charlier et al, 2010; Dedouit et al, 2014; Kristóf et al, 2015; Mihanović et al, 2017; Nilsson et al, 2010), the results of the scientific investigations, limited in time and analyses by the ecclesiastical authorities, evidenced no major discordance between the osteobiography of the skeletal remains and the historical accounts of their supposed identity (the slight discrepancy between the radiocarbon dating and period of life of Saint Nazarius may be explained by contamination with younger carbon). This collaboration between religious and scientific entities permitted to support the authenticity of the relics and historical accounts of this religious figure and provided additional information on the life of this individual.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Thus, in a similar approach as other studies verifying the authenticity of religious relics (Alterauge et al, 2016; Charlier et al, 2010; Dedouit et al, 2014; Kristóf et al, 2015; Mihanović et al, 2017; Nilsson et al, 2010), the results of the scientific investigations, limited in time and analyses by the ecclesiastical authorities, evidenced no major discordance between the osteobiography of the skeletal remains and the historical accounts of their supposed identity (the slight discrepancy between the radiocarbon dating and period of life of Saint Nazarius may be explained by contamination with younger carbon). This collaboration between religious and scientific entities permitted to support the authenticity of the relics and historical accounts of this religious figure and provided additional information on the life of this individual.…”
Section: Resultsmentioning
confidence: 65%
“…In a similar approach, the application of methods generally used in the forensic anthropology field to the analysis of human remains recognized by the ecclesiastical authorities as particular people of veneration and cult can permit the realization of an osteobiography of the individual. These results can then be compared with the information available about the lives and deaths of these historical figures through hagiographic texts, which are biographies of saints recognized by ecclesiastical authorities, as well as other historical sources, to either support or deny their authenticity (Alterauge et al, 2016; Charlier et al, 2010; Dedouit et al, 2014; Kristóf et al, 2015; Mihanović et al, 2017; Nilsson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the exhumation and analysis of Tycho Brahe's remains was at least in part to determine if the sixteenthcentury astronomer had been murdered (Rasmussen et al 2013). Other recent examples include identifying the body of St. Paul (Mihanović et al 2017) and examining the life history of famous castrato singer Farinelli (Belcastro et al 2011). Whether or not all such studies have a scientific rationale, this avenue of inquiry can provide important methods drawn from forensic anthropology as well as powerful examples of life histories reconstructed from physical evidence in skeletal remains.…”
Section: Biographical Approaches Within Bioarchaeologymentioning
confidence: 99%
“…The lapse of time can be months or years, but as we shall see, sometimes can be even centuries and millennia. Research on historical cases support this claim (Mihanović et al, 2017;Appleby et al, 2015;Dedouit et al, 2014a;Kristóf et al, 2015) but especially interesting cases are those of the remains with mummified tissues, as the preserved soft tissue and skeletal remains allow for the evaluation of pathological findings and assessment of the probable cause of death. For example, the study of a young male mummy from Peru revealed him to be a part of a sacrifice ritual (Cobo, 2010).…”
Section: Introductionmentioning
confidence: 98%